ANALISIS KOMITMEN LAYANAN DAN KAPABILITAS LAYANAN TERHADAP WORD OF MOUTH (WOM) DENGAN CITRA LAYANAN SEBAGAI INTERVENING VARIABEL - Andi - Setiawan (Admisi dan Bisnis, 2014)
This article examine the structural modeling Word Of Mouth (WOM) through service as a background image of the main article. The formulation of specific objectives of this article is to determine the most dominant variable affecting image WOM through service. In this article the analysis tool will test the effect of each independent variable and tied well with the approach of the Structural Equation Model (SEM). Another virtue of this article, is the formulation of a model of WOM through image management services in the area of customer cooperation. The main outcomes of the model in this article is to give positive suggestions for decision makers. Variables to be measured and tested in this article is the service commitment, capability of service, image service and Word Of Mouth (WOM). Accidental sampling method is a sampling technique, while for analytical techniques that are used confirmatory factor analysis and Regression Weight, on the SEM using AMOS 18.0 computerized package. The results of the analysis showed the capabilities of the service is the dominant variable or the greatest effect on Word Of Mouth